A 3D porous KCuFC/collagen fibers/gelatin adsorbent for ultra-fast cesium capture from radioactive wastewater - Xiaoxia Ye; Shanyuan Chen; Juan Liu; Yuling Tang; Jianfei Zhou; Wei Luo; Jie Chen (Bioresource Technology, 2026)

Dynamic soft-templating of highly polymerized carbon nitride enabling potentiated visible light-driven NH2Cl activation: A synergistic self-amplifying ROS/RNS cascade toward water remediation - Xingbo Yin; Qixun Zou; Yaqi Yong; Xiaowei Huo; Xin Cheng; Yuling Tang; Jiguang Du; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

α-Ketoglutarate attenuates ammonium chloride-induced ferroptosis by maintaining mitochondrial homeostasis in grass carp (Ctenopharyngodon idellus) hepatocytes - Yuling Zhang; Chengchen Jiang; Dapeng Li; Rong Tang (Aquatic Toxicology, 2026)

High CO2 coupled with nitrogen deprivation increases carbon capture and eicosapentaenoic acid production by a marine diatom after short-term induction - Yuling Yang; Shuyu Xie; Meijia Jiang; Siwei Tang; Junxiao Zhang; Guang Gao (Journal of Applied Phycology, 2026)

Long-term trends and risk regulation of heat exposure in megacities: seasonal dynamics and determinants - Ziwen Jin; Shuyi Zhang; Ke Zeng; Muyao Ma; Yue Yang; Yuling Fu; Hanxin Tang; Shan Yin; Ji Zheng; Min Liu (Environment, Development and Sustainability, 2026)

Characteristics and Mechanisms of Crack Propagation in Gas-Bearing Coal Under Adsorptive Versus Non-Adsorptive Gas Conditions - Dengke Wang; Yixuan Tang; Wenrui Li; Hongtu Zhang; Biao He; Furu Kang; Shixing Fan; Baisheng Nie; Yuling Xia; Xiaofei Pang; Jinhao Yu (Natural Resources Research, 2026)

Spatially explicit process-resolved fluxes and microbial drivers: Linking community succession to greenhouse gas emissions from full-scale industrial wastewater treatment - Weiwei Kong; Rui Dai; Zhaohui Yang; Qinyang Li; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Water Process Engineering, 2026)

Constructing a Z-scheme heterojunction on leather waste-derived biochar supporting graphitic carbon nitride for highly-efficient photocatalysis toward water decontamination - Liming Zhao; Rui Dai; Yuling Tang; Xin Cheng; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Anchoring free chlorine on carbon nanotubes to drive nonradical oxidation: interfacial binding-mediated complex generation enabling contaminant abatement - Qixun Zou; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2026)

Integrated metabolomics to systematically monitor quality indicators and metabolic dynamics in stored Ophiocordyceps sinensis - Chuyu Tang; Yuejun Fan; Bing Jia; Haoxu Tang; Yuling Li; Xiuzhang Li (Food Chemistry, 2026)

SFG enhances apoptosis of hepatocellular carcinoma by inhibiting tunneling nanotubes-mediated mitochondrial transport in the tumor microenvironment - Shasha Kong; Yuling Liu; Ruying Tang; Hui Li; Hongmei Lin; Longfei Lin (Apoptosis, 2026)

Non-linear and temporally dynamic effects of built environment and trip attributes on metro competitiveness - Yuqing Zhou; Xiao Fu; Yuling Xie; Tianli Tang; Guonian Lü (Journal of Transport Geography, 2025)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Distribution, ozone formation potential, and health risk assessments of VOCs in automotive seat cushion leather during finishing process - Zhaohui Yang; Chuanhui Mu; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Hazardous Materials, 2025)

Cuproptosis is involved in small intestinal toxicity in the paraffins during pregnancy - Juan Tang; Zemin Xu; Mengna Jiang; Chao Luo; Xiaoyan Li; Yuling Jiang; Yi Qu; Jialing Ruan; Xiaoke Wang; Meihua Zheng; Wing-Cheung Law; Xinyuan Zhao (Toxicology Letters, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Exothermicity analyses and energy efficiency of a novel liquid cooling strategy in suppressing thermal runaway propagation of a lithium-ion battery module - Hanyu Zhao; Xuguang Tang; Lun Li; Junhui Gong; Yuling Xiao (Process Safety and Environmental Protection, 2025)

Human FABP7 selectively captures docosahexaenoic acid over eicosapentaenoic acid: A potential protein-based platform for affinity purification of ω-3 lipids - Yuling Tang; Xunjiao Wei; Yonghua Wang; Wen Chen (Food Bioscience, 2025)

Efficient antibiotic tetracycline degradation and toxicity abatement via the perovskite-type CaFexNi1-xO3 assisted heterogeneous electro-Fenton system - Yuling Liang; Aochen Feng; Naif Abdullah Al-Dhabi; Jing Zhang; Wenle Xing; Tao Chen; Yuxuan Han; Guangming Zeng; Lin Tang; Wangwang Tang (Water Research, 2025)

Characteristics of lipid accumulation induced by high-altitude environment improve the total antioxidant capacity of Ophiocordyceps sinensis - Tao Wang; Chuyu Tang; Mengjun Xiao; Min He; Yuling Li; Xiuzhang Li (Food Chemistry, 2025)

Innovative sulfhydryl and ZIF-7-NH2 functionalized leather collagen fibers for selective and efficient removal of Hg(II) - Jie Chen; Huiyao Huang; Zhihao Wu; Xiaoxia Ye; Yuling Tang; Jianfei Zhou; Bi Shi (Process Safety and Environmental Protection, 2025)

AIE-based dual-ratiometric chemosensor for detection of sulfur dioxide derivatives and viscosity and its application in food samples and biological imaging - Na Tang; Ruian Sun; Kangshuo Xu; Haichang Ding; Yuling Zeng; Yuan Ji; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

Transcriptomics and metabolomics provide the difference of unique odor between natural and cultivated Ophiocordyceps sinensis and the biosynthetic pathway of key volatile compounds - Tao Wang; Mengjun Xiao; Chuyu Tang; Jianzhao Qi; Yuling Li; Xiuzhang Li (Food Bioscience, 2025)

Encapsulation of oleanolic acid into cyclodextrin metal-organic frameworks by co-crystallization: Preparation, structure characterization and its effect on a zebrafish larva NAFLD model - Meng Li; Dongxia Hu; Dian Zhang; Guangya Xu; Di Wu; Chengcheng Gao; Linghan Meng; Xiao Feng; Weiwei Cheng; Zhenjiong Wang; Yuling Yang; Xiaozhi Tang (Food Research International, 2025)

Emission characteristics and probabilistic health risk of volatile organic compounds from leather sofa - Chuanhui Mu; Yuling Tang; Zhaohui Yang; Jianfei Zhou; Bi Shi (Journal of Environmental Sciences, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

A turn-off xanthene-based fluorescent probe for detection of cysteine and its practical application in bioimaging and food samples - Na Tang; Kangshuo Xu; Ruian Sun; Haichang Ding; Yuling Zeng; Yuan Ji; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2024)

Simultaneous removal of CTRX and Cr(Ⅵ) by CQDs-doped bifunctional molecular imprinted BiOCl/Bi3NbO7 photocatalyst: The enhanced selective performance and charge separation abilities - Huining Zhang; Yankui Xiao; Zongqian Zhang; Jianping Han; Zhiguo Wu; Zhiqiang Wei; Ying Zhu; Qi Guo; Lihong Tian; Yuling Tang (Journal of Environmental Chemical Engineering, 2024)

Identification of Dalbergiae Odoriferae Lignum active ingredients and potential mechanisms in the treatment of adriamycin-induced cardiotoxicity based on network pharmacology and experimental verification - Yuling Luan; Xinyue Ding; Lingxiao Zhang; Shuyan Huang; Chenghao Yang; Yueer Tang; Lina Xing; Hui Zhang; Zongjun Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Epidemiologic trends and changes in humoral immunity and lymphocyte subsets levels among hospitalized children with Mycoplasma pneumoniae infection during 2019–2023 - Linyan Tang; Kaiwen Zheng; Lanlan Ma; Ling Chen; Yuling Zhao; Li Li; Ke Wang; Jing Zhang; Xing Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Photocatalytic removal of ammonia nitrogen from water: investigations and challenges for enhanced activity - Huining Zhang; Yang Cao; Shaofeng Wang; Yuling Tang; Lihong Tian; Wenrui Cai; Zhiqiang Wei; Zhiguo Wu; Ying Zhu; Qi Guo (Environmental Science and Pollution Research, 2024)

3D visualization of oil-abundant limon flavedo layer under drying - Sara Shamim; Zhenting Wu; Yuling Tang; Jingru Jia; Chunju Liu; Haiou Wang; Fangcheng Zheng; Long Ba (Journal of Food Engineering, 2024)

Antibiotic resistance, biofilm formation, and molecular epidemiology of Staphylococcus aureus in a tertiary hospital in Xiangyang, China - Yitong Tang; Na Xiao; JiuMing Zou; Yuling Mei; Yue Yuan; Menghuan Wang; Zezhou Wang; Yunjuan Zhou; Yiyuan Chen; Shichao Li (Brazilian Journal of Microbiology, 2024)

Research progress of microfluidics-based food safety detection - Wenjun Jiang; Qu Tang; Yidan Zhu; Xijuan Gu; Li Wu; Yuling Qin (Food Chemistry, 2024)

Neutral pH photoenzymatic activity of Au-doped g-C3N4 nanosheet for colorimetric detection of total antioxidant capacity in food samples - Xianming Li; Wentong Fan; Honghu Tang; Dongdong Li; Yuling Xiao; Bin Yang; Yi Zhao; Peng Wu (Food Chemistry, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

Cr and N co-doped biochar driving controllable peroxydisulfate activation pathways to degrade tetracycline: Pyrrolic N inducing singlet oxygen generation - Lijun Guo; Liming Zhao; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2024)

Lithologic control of priming effect in subtropical forest - Tiangang Tang; Qi Zhang; Ruitong Fu; Pengpeng Duan; Yuling Zhang; Xinyi Yang; Kelin Wang; Dejun Li (CATENA, 2024)

The photo- and microbial degradation kinetics and pathways of sulfadoxine in seawater elucidated by liquid chromatography coupled with time-of-flight mass spectrometry - Guowen Tang; Yuling Chen; Shanshan Lin; Xiaolin Li (Chemosphere, 2024)

Energy consumption and carbon emissions management in drinking water treatment plants: A systematic review - Mohamed Yateh; Fengting Li; Yuling Tang; Cheng Li; Bin Xu (Journal of Cleaner Production, 2024)

Improving the freeze-thaw stability of fish myofibrils and myofibrillar protein gels: Current methods and future perspectives - Xiao Feng; Xi Yu; Yuling Yang; Xiaozhi Tang (Food Hydrocolloids, 2023)

Wheat adaptation to environmental stresses under climate change: Molecular basis and genetic improvement - Hude Mao; Cong Jiang; Chunlei Tang; Xiaojun Nie; Linying Du; Yuling Liu; Peng Cheng; Yunfeng Wu; Huiquan Liu; Zhensheng Kang; Xiaojie Wang (Molecular Plant, 2023)

Construction of starch-sodium alginate interpenetrating polymer network and its effects on structure, cooking quality and in vitro starch digestibility of extruded whole buckwheat noodles - Xiang Xu; Linghan Meng; Chengcheng Gao; Weiwei Cheng; Yuling Yang; Xinchun Shen; Xiaozhi Tang (Food Hydrocolloids, 2023)

Boron doping g-C3N4 supported Cu2O for photocatalytic reforming of xylose into lactic acid - Yanting Lv; Weiyong Shao; Yuling Kong; Nanhua Li; Xinrui Huang; Zhihao Tang; Murong Gong; Lizi Li; Weiqi Wei (Journal of Environmental Chemical Engineering, 2023)

Coconut shell biochar application in liquid-solid microextraction of triazine herbicides from multi-media environmental samples - Mengge Ma; Zongliang Niu; Zhuhua Tang; Jinyang Bai; Bei Li; Yuling Zhou; Yingying Wen (Analytica Chimica Acta, 2023)

Quinoa protein Pickering emulsion: A promising cryoprotectant to enhance the freeze-thaw stability of fish myofibril gels - Kaiyue Cen; Caoxing Huang; Xi Yu; Chengcheng Gao; Yuling Yang; Xiaozhi Tang; Xiao Feng (Food Chemistry, 2023)

Chrome shaving-derived biochar as efficient persulfate activator: Ti-induced charge distribution modulation for 1O2 dominated nonradical process - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Science of The Total Environment, 2023)

Water deficit aggravated the inhibition of photosynthetic performance of maize under mercury stress but is alleviated by brassinosteroids - Yulou Tang; Junjie Zhang; Lijuan Wang; Hao Wang; Haochi Long; Liuyang Yang; Gengwei Li; Jiameng Guo; Yongchao Wang; Yuling Li; Qinghua Yang; Weiyu Shi; et al. (Journal of Hazardous Materials, 2023)

Changes in the physicochemical, structural and emulsifying properties of chicken myofibrillar protein via microfluidization - Keying Han; Xiao Feng; Yuling Yang; Xiaozhi Tang; Chengcheng Gao (Innovative Food Science & Emerging Technologies, 2023)

Peroxydisulfate activation using Fe, Co co-doped biochar and synergistic effects on tetracycline degradation - Lijun Guo; Liming Zhao; Yuling Tang; Jianfei Zhou; Bi Shi (Chemical Engineering Journal, 2023)

Preparation of Functionalized Graphene Oxide Composite Spheres and Removal of Cu2+ and Pb2+ from Wastewater - Huining Zhang; Xingmao Liu; Lihong Tian; Yuling Tang; Zhongyu Shi; Yankui Xiao; Zhiguo Wu; Ying Zhu; Qi Guo; Zhangpu Peng (Water, Air, & Soil Pollution, 2022)

Protective effects of SP600125 on mice infected with H1N1 influenza A virus - Yuling Tang; Guanghui Yang; Yuxiang Li; Ming Wang; Gebin Li; Yanxin Hu (Archives of Virology, 2021)

Assessment of long-term functional maintenance of primary human hepatocytes to predict drug-induced hepatoxicity in vitro - Yi Chen; Dan Tang; Hongping Wu; Yuling Wu; Tianjie Yuan; Hongdan Zhang; Yingfu Jiao; Weifeng Yu; Hexin Yan (Archives of Toxicology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)

Generation and Screening of T-DNA Insertion Mutants Mediated by Agrobacterium tumefaciens in the Garden Asparagus Stem Blight Pathogen Phomopsis asparagi - Yueping Zhang; Huaxiang Qu; Ping Zhao; Yongping Tang; Jingsong Zhou; Shaochun Luo; Yuling Yin; Guangyu Chen (Current Microbiology, 2017)

Novel antimicrobial metabolites produced by Sika deer-associated Actinomyces sp. JN411010 - Yujiao Tang; Yanmei Wang; Zhaohui Wang; Jing Zhang; Jianchun Qin; Quankai Wang; Lihua Yang; Lingzhi Xu; Yuling Ding; Yang Guo; Hongliang Li; Jingsi Li; et al. (Natural Product Research, 2013)

Erratum to: Flavokawain B induces apotosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)

Flavokawain B induces apoptosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)